Respostas

2014-03-01T16:17:29-03:00
4x -24 -2x = 5x+3
4x -2x -5x = 3 + 24
2x - 5x =27
-3x=27
x=27
    3
x=9

2(x -2) +8 (-x +3) =0
2x -4 -8x + 24 =0
2x-8x =4 -24
-6x= -20
x=-20
     6

2014-03-01T16:40:28-03:00
4x - 24 - 2x = 5x + 3
4x - 2x - 5x = 3 + 24
- 3x = 37
x = 27 
÷ (- 3)
x = - 9

------------------------------------------------------------------------------------------------

2 (x - 2) + 8 (- x + 3) = 0
2x - 4 - 8x + 24 = 0
2x - 8x = - 24 + 4
- 6x = - 20
x = - 20 ÷ (- 6)
x = 20/6
x = 10/3